Evaluation of the dried blood spot (DBS) collection method as a tool for detection of HIV Ag/Ab, HBsAg, anti-HBs and anti-HCV in a Malaysian tertiary referral hospital - Lee, C.E.; Sri Ponnampalavanar, S.; Syed Omar, S.F.; Mahadeva, S.; Ong, L.Y.; Kamarulzaman, A. (2011)
INTRODUCTION: Dried blood spot (DBS) collection is an appealing alternative to whole blood or plasma sampling, as it has technical and economic advantages over the latter. MATERIALS AND METHODS: A prospective cross-sectional study was conducted at a Malaysian tertiary referral hospital from November 2009 to March 2010. One hundred and fifty paired specimens of DBS and plasma were analysed by the standard assays for HIV Ag/Ab, HBsAg, anti-HBS and anti-HCV, separately (total 600 paired specimens). DBS sample titres were then compared to the results of plasma testing, which was used as the gold standard. RESULTS: For the HIV Ag/Ab assay with a cut-off point of 0.35 Relative Light Units (RLUs), the sensitivity and specificity were both 100%. For the HBsAg assay, the sensitivity was 96.5% and the specificity was 97.8%, with a cut-off point of 1.72 RLUs. Sensitivity for the anti-HBs test was 74.2% and the specificity was 86.9%, using a cut-off point of 0.635 RLUs. For the anti-HCV assay, the sensitivity was 97.3% and the specificity was 100%, with a cut-off point of 0.10 RLUs. CONCLUSION: DBS is an ideal choice to be used as a screening tool for the detection of HIV, Hepatitis B and Hepatitis C virus infections. However, different cut-off values need to be used for the validation of test positivity in DBS samples because the small amount of blood in the DBS specimens leads to lower assay titres.